Teknologi konversi biomassa kelapa sawit (palm kernel meal) menjadi bioetanol secara enzimatis: tinjauan literatur - Serarifi Elagin Harahap; Erliza Hambali; Erliza Noor; Khaswar Syamsu (AGROINTEK, 2026)
The palm oil industry is a major agricultural sector in Indonesia. This sector produces a significant amount of biomass, including palm kernel meal (PKM), which has tremendous potential as a sustainable feedstock for second-generation bioethanol production. This review aims to explore the enzymatic conversion of PKM to bioethanol as an environmentally friendly and feasible alternative to fossil fuels. The scope of the study covers pretreatment, enzymatic saccharification, fermentation, and purification technologies, with an emphasis on strategies that optimise sugar release and ethanol yield. A literature review method was used, analysing publications from 2010 to 2025 sourced from Google Scholar and Web of Science, filtered based on their relevance to PKM utilisation and bioethanol production. The results show that PKM, which is rich in cellulose and hemicellulose, can be effectively hydrolysed using enzyme consortia that include endomannanase, β-mannosidase, and cellulase, achieving high sugar conversion rates. Pretreatment methods including autoclaving and hot water were found to increase enzyme accessibility, while fermentation through simultaneous saccharification and fermentation (SSF) showed higher ethanol yields compared to separate hydrolysis and fermentation (SHF). In addition, bioethanol purification through a combination of distillation and adsorption achieved a fuel purity of 99.5%. Overall, the enzymatic conversion of PKM into bioethanol not only provides renewable energy but also contributes to waste reduction.